3 A review of the magnitude of financial relationships with industry and disclosure practices among clinical practice guideline authors. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Wayant, Cole; Vassar, Matt
Abstract : Objectives: Financial conflicts of interest (FCOI) with the pharmaceutical industry are associated with a sizeable, unidirectional, reproducible effect in favor of 'positive' research findings, per a recent Cochrane systematic review. In the context of clinical practice guidelines (CPG) — consensus documents that singularly guide most aspects of patient care — FCOI may result in biased treatment recommendations. Here, to derive a summary effect of the the magnitude of financial relationships with industry among CPG authors, and the accuracy of relationship disclosure, we synthesize both published and unpublished investigations. Method: Our protocol is publicly available (https://osf.io/MXF4B/). Using a combination of a PubMed search and expert knowledge of available studies, we gathered all published investigations of CPG author financial relationships with industry. Included studies must have used the OpenPayments database to either: 1) quantify the magnitude of financial relationship or 2) assessed the accuracy of disclosure statements among CPG authors. Raw payments data were solicited from all previous studies and converted to money received per author per 1 year. We combined raw payment data to derive summary measures of central tendency (e.g., medians with interquartile ranges (IQR)) for all four categories of OpenPayments data: General (e.g., personal fees such as speaking or honoraria), Research (e.g., direct costs), Associated research (e.g., grants), and Ownership (e.g., stock). We use Stata 15.1 and the command metaprop to conduct a fixed-effect meta-analysis of the proportion of disclosure statements that were accurate across all eligible studies. Results: All data (including area of medicine) and figures are available via OSF (https://osf.io/MXF4B/). A total of 10 studies (4 published, 6 under journal review by our team) with raw payments data comprising 494 CPG authors were retrieved for our analysis of the magnitude of financial relationships. Across all 494 CPG authors, the median total money received from industry per year was 14, 286 (IQR 105, 964). Authors who received money in each category received (median, IQR): General payments 4, 141 (IQR 20, 641); Research 3, 155 (IQR 5, 396); Associated Research 66, 541 (IQR 253, 552); Ownership 7, 199 (IQR 121, 417). A total of 9 studies investigated the accuracy of CPG author disclosure using OpenPayments database. The pooled accuracy of disclosure was 18% (95%CI 16% - 20%). One included study represented 62% of the weight in the meta-analysis. In a sensitivity analysis removing this study, the pooled accuracy of disclosure was 30% (95%CI 27% - 34%). Conclusions: The results of this novel synthesis demonstrate that authors of medical CPGs are heavily conflicted and are likely not representative of most physicians. To curb the effects of FCOI on CPGs, international policy collaborations are necessary to 1) track payments to non-US based physician-authors; 2) improve disclosure of existing FCOIs; 3) encourage divestiture and prevention of future FCOIs.